Effect of E-Commerce Business and Technology Based Accounting Information Systems on the Need for Company Audit Services - D Dassaad; Dyah Palupi; R Riyanti; Imam Purwanto (IJISTECH (International Journal of Information System and Technology), 2022)
The background of this research is how to find out the variables that can affect a company, especially in the field of audit architects. With a company audit, the advantages and disadvantages of a company can be known. Therefore, knowing the variables that know the shortcomings of the company will be able to help add value to the company. The method used in this research is how to use the literature review method and survey method to 100 employees which was carried out randomly so that real data can be seen in the field. Therefore, this research method will be able to assist researchers in determining a clear research direction. The problem raised in this research is how to find out the relationship between e-commerce and accounting information systems to the audit needs of a company, with an audit, the direction and goals of the company can be known in the future. This study aims to find out the direction of the company's goals in order to be able to develop the company, especially in business development in the field of marketing in the field of commerce, by incorporating accounting information systems. Then accounting information system and audit system.